Gender mainstreaming in European policy: Innovation or deception? - Alison E. Woodward (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
Mainstreaming, an approach aimed at making policy more gender sensitive, has been taken globally on board by countries with widely varying policy machineries. This social innovation was launched in the context of Bejing 1995 by a network of women's movement activists, academics and politicians sometimes referred to as State Feminists. As a policy strategy for change, it utilizes the language of efficiency current in circles hoping to rationalize public bureaucracy. Yet, because it deals with gender, mainstreaming also illustrates, in a particularly provocative way, some more general problems in political innovation. Mainstreaming provides a good illustration of the paradoxes and ambiguities of gender as a motor for change in political organization. Mainstreaming seems to offer the potential to recoup the power of definition by making the image of the citizen behind the policy more 'evident' and erasing the premise of gender neutrality. The trick is carried out through the insertion of 'tools' like Trojan horses inside the policy process, using 'formal rationality' to reveal gender related negotiations. This paper provides an initial discussion of the ways in which the mainstreaming approach aims at changing the definitions of the situation in government and secondly suggests factors that may affect whether the approach will actually succeed in various settings. It offers a framework for a consideration of the conditions necessary to ensure that mainstreaming becomes an institutional innovation and leads to gender being included in policy making as a given. It tests this using observations from the European Commission, Denmark, Sweden, the Netherlands and regional and federal government in Belgium. The role of women's organizations, state feminist machinery, academics and policy frameworks are crucial variables to help predict whether mainstreaming remains rhetoric or becomes a useful approach to changing policy. – – Mainstreaming, ein Ansatz zur Erhöhung der Geschlechtssensibilität von Politik, ist inzwischen weltweit von Ländern mit sehr unterschiedlichen politischen Strukturen übernommen worden. Diese soziale Innovation wurde im Kontext der Weltfrauenkonferenz in Peking 1995 von einem Netzwerk ins Leben gerufen, das sich aus Mitgliedern der Frauenbewegung, Wissenschaftlerinnen und Politikerinnen (manchmal "Staatsfeministinnen" genannt) zusammensetzte. Als politische Strategie, die auf Veränderungen abzielt, benutzt sie die Rhetorik von Effizienz, die in Diskursen zur Rationalisierung öffentlicher Verwaltung geläufig ist. Aber weil ihr Gegenstand das Geschlechterverhältnis ist, beleuchtet Mainstreaming in besonders herausfordernder Weise allgemeinere Probleme politischer Innovation. Mainstreaming illustriert nachdrücklich die Paradoxien und Zwiespältigkeiten, die der Einsatz von "gender" als Motor für Veränderungen politischer Organisationen impliziert. Der Ansatz des Mainstreaming birgt möglicherweise das Potential, die Definitionsmacht zu verändern, indem er die Person des Bürgers/der Bürgerin verdeutlicht, auf den/die sich Politiken beziehen und indem er die Annahme von Geschlechtsneutralität in Frage stellt. Dies gelingt durch die Einführung von Instrumenten in den politischen Prozeß - vergleichbar einem Trojanischen Pferd -, wobei "formale Rationalität" genutzt wird, um die Geschlechtsspezifik von Aushandlungsprozessen aufzudecken.
Keywords: 330; Frauenpolitik; Politikberatung; EU-Politik; Theorie; EU-Staaten; Gender Mainstreaming